PENDIDIKAN NILAI DAN MASA DEPAN BANGSA - Wira Sugiarto (Akademika: Jurnal Keagamaan dan Pendidikan, 2019)
Universal values are increasingly difficult to find in Indonesia. The reform movement that was designed to improve the fate of the nation turned out to be unable to improve the Indonesian nation. The various crises that hit Indonesia have made the Indonesian people increasingly critical and uncertain of their direction. The normless condition can be seen from the behavior of the Indonesian people who tend to be undisciplined, corrupt, manipulated, and disobedient to the law, fanaticism and other destructive behavior. This condition resulted in a moral crisis that threatened the destruction of the nation. The moral crisis is one of the nation's crucial problems at the moment so it needs awareness to fix it. We are very concerned to see the children of the nation who live without a strong moral foundation. The behavior of the nation's children in all fields increasingly deviates from the applicable values and provisions. Anti-social attitudes are also growing. It seems that the Indonesian people are not heading towards the process of nation-building as a whole but towards the process of destruction.Nilai-nilai universal semakin sulit ditemukan di Indonesia. Gerakan reformasi yang dirancang untuk memperbaiki nasib bangsa ternyata belum mampu memperbaiki bangsa Indonesia. Berbagai krisis yang melanda Indonesia telah membuat bangsa Indonesia semakin kritis dan tidak tentu arah tujuannya. Kondisi normless dapat dilihat dari perilaku bangsa Indonesia yang cenderung tidak disiplin, korupsi, manipulasi, tidak taat hukum, sikap fanatik dan perilaku merusak lainnya. Kondisi ini menghasilkan krisis moral yang mengancam kehancuran bangsa. Krisis moral merupakan salah satu persoalan bangsa yang sangat krusial saat ini sehingga perlu kesadaran untuk memperbaikinya. Kita sangat prihatin melihat anak-anak bangsa yang hidup tanpa landasan moral yang kuat. Perilaku anak bangsa dalam semua bidang semakin menyimpang dari nilai dan ketentuan yang berlaku. Sikap anti-sosial pun semakin berkembang. Tampaknya bangsa Indonesia tidak sedang menuju proses pembangunan bangsa seutuhnya tetapi menuju proses kehancuran.___________________Keywords: Pendidikan Nilai, Karakter Bangsa.